A novel high-strain-rate ferrite dynamic softening mechanism facilitated by the interphase in the austenite/ferrite microstructure. (March 2017) - Haghdadi, N.; Cizek, P.; Beladi, H.; Hodgson, P.D.
Abstract: The ferrite softening mechanisms in the austenite/ferrite microstructure have been comprehensively examined as a function of the strain rate at a high deformation temperature. For this purpose, a 23Cr-6Ni-3Mo duplex stainless steel was used having the microstructure specifically designed to contain an extremely low fraction of the pre-existing ferrite/ferrite high-angle boundaries, which are generally expected to provide preferential discontinuous dynamic recrystallization (DDRX) nucleation sites. The deformation was performed in uniaxial compression at 1000 °C using strain rates of 0.1 and 10 s −1 and a detailed microstructural analysis was conducted, including the determination of dislocation Burgers and line vectors, dislocation density and stored energy. The softening mechanism within ferrite at the low strain rate used has been classified as continuous dynamic recrystallization (CDRX), characterised by a progressive conversion of low-misoriented subgrains into (sub)grains delineated partly by low-angle and partly by high-angle boundaries. In contrast to the current widespread view, it has been revealed that a marked increase in the strain rate leads to a transition in the softening mechanism from CDRX towards a novel mechanism analogous to DDRX. The latter mechanism involves the formation of new grains through the growth of the highly-misoriented subgrains, preferentially formed in the ferrite/austenite interphase mantle regions. Graphical abstract: Image 1